2020
DOI: 10.3390/cancers12010191
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma and Thrombosis: Prophylaxis and Risk Prediction Tools

Abstract: Thromboembolism in multiple myeloma (MM) patients remains a common complication that renders the optimization of our thromboprophylaxis practice necessary. This review aims to make clear the need for the development of more accurate risk assessment tools and means of thrombosis prevention. Current clinical practice is guided by available guidelines published by the IMWG in 2014, but the extent to which these are implemented is unclear. Recently, several groups developed clinical scores for thrombosis risk in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 105 publications
(122 reference statements)
1
60
0
9
Order By: Relevance
“…The poor concordance with IMWG guidelines regarding ASA or LMWH use for VTE prophylaxis in MM patients has been well documented in other studies dealing with "real life" experiences [48]. A retrospective French study conducted on 236 patients treated with an IMiDs-based regimen demonstrated that only 43% high-risk and 34% low-risk patients received a thrombo-prophylaxis [19].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The poor concordance with IMWG guidelines regarding ASA or LMWH use for VTE prophylaxis in MM patients has been well documented in other studies dealing with "real life" experiences [48]. A retrospective French study conducted on 236 patients treated with an IMiDs-based regimen demonstrated that only 43% high-risk and 34% low-risk patients received a thrombo-prophylaxis [19].…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for the poor adherence of physicians to the IMWG indications could be related to the fact that the definition of the risk of developing a VTE remains too vague and the different parameters used to define the risk are equally considered, while they have probably a different strength as risk factors [48,49]. For example, the use of erythropoietin is considered a risk factor in the same way as others, but it must be taken into account that erythropoietin increases the risk of developing VTE especially when it determines a significant increase in hematocrit and hemoglobin (Hb) [19,55].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations